Using social proof techniques in a brick and mortar grocery retailer to promote healthy, fresh fish products - Joseph Karlton Gallogly 1993- (2019)
There is an across the board agreement that fresh fish is a healthy food and it provides vital nutrients that are essential in leading a healthy lifestyle. While the benefits of eating fish are clear, consumers often are apprehensive when purchasing fresh fish both in-store and online. Social proof techniques have often been used online as a way of promoting certain products. In this paper, these techniques are applied to fresh fish to determine if they are applicable to fish purchasing in a physical retail environment. In a grocery store in Reykjavík, Iceland, a choice-based conjoint (CBC) analysis along with in-store experimentation are used to understand the relationship, or lack thereof, of social proof techniques and fresh fish purchasing. The primary interventions in both the CBC analysis and the in-store experimentation are product labels that call out an item as being a “Top Seller” or “Store’s Choice” These labels have been modeled after Amazon’s social proof labels of the same variety. The integration of these online principles into an offline setting are consistent with the current call for an evolution of the brick and mortar stores. This trend has been made popular by retail experts such as Herb Sorensen who argue that the future of retail relies on its ability to adapt to the coming digital age. For brick and mortar retailers to compete with online stores, they must think like online stores. The results gathered from this research show that social proof marketing techniques are effective in the marketing of fresh fish products. This information can be used by retail managers to have a better understanding of possible tactics to promote fresh fish sales.